Architecture of New Rare Earth Metal Complexes as Precursors for the Fabrication of a New Class of OLEDs with Blue Shift Fluorescence. Issue 5 (22nd July 2020) - Darzinezhad, Khodabakhsh; Amini, Mostafa M.; Mohajerani, Ezeddin; Fathollahi, Mohammad‐Reza; Janghouri, Mohammad; Notash, Behrouz; Rostami, Aghil
Abstract : Due to the high demand for blue organic light‐emitting diodes (blue‐OLED), in this work, a new class of them with lanthanide complexes is engineered based on a chemical design. Four new rare‐earth metals complexes, Nd2 (C11 H9 NO)4 (NO3 )4 (CH3 COO)2 · 2(CH3 OH) (1 ), Pr2 (C11 H9 NO)4 (NO3 )4 (CH3 COO)2 · 2(CH3 OH) (2 ), Sm2 (C11 H9 NO)4 (NO3 )4 (CH3 COO)2 · 2(CH3 OH) (3 ), and Tm2 (C11 H9 NO)4 (NO3 )4 (CH3 COO)2 · 2(CH3 OH) (4 ) as new precursors for fabrication of blue‐OLED were synthesized using 8‐hydroxy‐2‐methylquinoline as the primary ligand. The synthesized complexes were characterized by UV/Vis and infrared spectroscopy, elemental analysis, and X‐ray powder diffraction. The molecular structure of 1 and 2 as representative complexes were accomplished by single‐crystal X‐ray diffraction. The single‐crystal structures showed complexes 1 and 2 are iso‐structural. The similar X‐ray powder diffraction patterns of prepared complexes revealed the same structure for all of them. The results showed that the photoluminescence spectra of the complexes could scrutinize by the impact of rare‐earth metals. The strong blue fluorescence emission spectra of the prepared complexes showed they are suitable for the fabrication blue light‐emitting diodes using a simple processing method, and this may overcome the high demand of blue‐OLED. Abstract :